The performance of Islamic banking in comparison with conventional Banking in Malaysia from year 2001 - 2005 / Fara Dilla Tamrin - Tamrin, Fara Dilla (2006)
This study evaluates an inter-bank performance of Islamic bank and conventional bank in term of its profitability, liquidity and debt. Bank Islam Malaysia Berhad (BIMB) will represent the Islamic bank while conventional banks will be presented by 5 anchor banks in Malaysia (Bumiputra Commerce Bank Berhad, Hong Leong Bank Berhad, Malayan Banking Berhad, RHB Berhad and Southern Bank Berhad). The period taken for this study was five years (year 2001 until 2005) Methods used in this study are financial ratios and T-test (paired sample means). Financial ratios including profitability, liquidity and debt ratio can measure the banks' performances while T-test is used to determine their significance difference (5% significance level). The study can conclude that the performance of Islamic bank is equal in comparison to the conventional banks if the period was taken from year 2001 until year 2004. Meanwhile, if year 2005 was included as the sample period, then the performance of Islamic bank is not equal to the performance of conventional banks